Synthesis and characterization of sugar-bearing chitosan derivatives: Aqueous solubility and biodegradability - Park, JH; Cho, YW; Chung, H; Kwon, IC; Jeong, SY (AMER CHEMICAL SOC, 2003)
The extended use of chitosan in biomedical fields has been limited by its insoluble nature in a biological solution. To endow the water solubility in a broad range of pH, chitosan derivatives were prepared by the covalent attachment of a hydrophilic sugar moiety, gluconic acid, through the formation of an amide bond. These sugar-bearing chitosans (SBCs) were further modified by the N-acetylation in an alcoholic aqueous solution. Thereafter, the effect of the gluconyl group and the degree of N-acetylation (DA) on the water solubility at different pHs and on the biodegradability of chitosan were investigated. The SBCs showed the water solubility in a broader range of pH than chitosan, whereas they were still insoluble at neutral and alkali pH. The N-acetylation of SBCs significantly affected the water solubility, for example, the SBCs with the DA, ranging from 29% to 63%, were soluble in the whole range of pH. This might result from the improved hydrophilicity by the gluconyl group, accompanied by the role of the N-acetyl group that disturbed the hydrogen bonding between amino groups of chitosan. From the biodegradation tests, determined by the decrease in the viscosity of a polymer solution exposed to lysozyme, it was evident that the gluconyl group attached to chitosan improved the biodegradability. Thus, it was possible to control the biodegradability of chitosan by adjusting the amounts of gluconyl and N-acetyl groups in the chitosan backbone. The N-acetylated SBCs, soluble in the broad range of pH, might be useful for various biomedical applications.
Keywords: WATER-SOLUBLE CHITIN; N-SUCCINYL-CHITOSAN; MOLECULAR-WEIGHT; IN-VITRO; ACETYLATION; POLYSACCHARIDE; DEGRADATION; MICELLES; PROPERTY; CHAIN